Blockchain Abstract Architecture for Energy Collaboration for Agriculture in Indonesia based on Bibliometric Approach (Open International Journal of Informatics, 2024)
The direction of development for the application of electric vehicles is starting to be seen with great certainty, this situation is driven by the vision of sustainable development goals (SDGs) where one of them is energy that is minimal from carbon. The agricultural sector is a field of activity that also requires machinery or equipment to support its activities. and currently most of them still use conventional machines that produce quite high carbon, meanwhile, when agricultural machinery is converted to electricity, the challenge is to provide affordable energy at competitive prices and reliable technology. Blockchain is a disruptive technology that has many advantages, especially in terms of flexibility and security to accommodate broad interactions from many parties in an activity chain. The purpose of this research is to develop a blockchain-based architecture to support collaborative energy supply in agriculture that is sourced from renewable energy. we use Scopus indexed data sources to formulate and describe the directions and references of the proposed architecture